Beyond the online offline distinction: Entry points to digital discourse. (June 2020) - Bolander, Brook; Locher, Miriam A.
Abstract: Research in the field of digital discourse has increasingly highlighted the relevance of the blurring of borders between online and offline, and the convergence of different modes for the ways individuals use resources, including language, to engage in various socio-cultural practices. More recently some of this work has turned to focus on the methodological implications of these developments. Building on existing scholarship, this paper reviews a range of literature to probe the methodological implications of shifts in possible sites or "entry points" (Heller, Pietkäinen & Pujolar, 2018, 47) to digital discourse and changes in the scope of what counts as data. While we position our paper as a review on methodology, we argue for the importance of engaging with these questions as intricately related to epistemology, theory and the study of language more generally.